Caring task-involving climate leads to greater improvements in free-throw shooting biomechanics and motivational responses - Hogue, Candace M.; Cabarkapa, Dimitrije; Fry, Mary D.; Fry, Andrew C.; Wineinger, Troy O.; Chamberlin, Jacob M. (Frontiers in Psychology, 2025)
IntroductionThere is a need for experimental and cross-disciplinary research in sport psychology, particularly studies that incorporate objective performance assessments into motivational climate research.MethodsThis investigation examined biomechanical changes in athletes’ free-throw shooting form in response to the motivational climate during a basketball clinic, as well as affect, demand and resource appraisals, and motivational outcomes. Thirty-nine male basketball players were assigned to a free-throw clinic with either a caring, task-involving (CTI) climate, where high effort and improvement are valued and recognized and mistakes are part of learning or an ego-involving (EI) climate, where winning is prioritized, athletes are punished for mistakes, and star players are favored. Participants completed pre- and post-clinic surveys. Video analysis allowed for the assessment of free-throw kinematics (e.g., knee flexion) pre- and post-clinic.ResultsNo baseline group differences were found. At post-assessment, the CTI group’s shooting kinematics more closely resembled those of proficient shooters compared to the EI group. Individuals in the EI climate perceived the clinic as more demanding and reported a significant increase in negative affect. In contrast, CTI participants reported significantly greater positive affect, effort, and interest and excitement to continue practicing.DiscussionFindings suggest creating a CTI climate can enhance motivation and facilitate player development.